Case Report: A novel mutation in WFS1 gene (c.1756G>A p.A586T) is responsible for early clinical features of cognitive impairment and recurrent ischemic stroke - Chen, Yuan; Zhang, Miao; Zhou, Yuying; Li, Pan (Frontiers in Genetics, 2023)
Wolfram syndrome 1 (WFS1) gene mutations can be dominantly or recessively inherited, and the onset of the clinical picture is highly heterogeneity in both appearance and degree of severity. Different types of WFS1 mutations have been identified. Autosomal recessive mutations in the WFS1 gene will underlie Wolfram syndrome 1 (WS1), a rare and severe neurodegenerative disease characterized by diabetes insipidus, diabetes mellitus, optic atrophy, deafness, and other neurological, urological and psychiatric abnormalities. Other WFS1-related disorders such as low-frequency sensorineural hearing impairment (LFSNHI) and Wolfram syndrome-like disease with autosomal dominant transmission have been described. It is difficult to establish genotype-phenotype correlations because of the molecular complexity of wolframin protein. In this report, we presented a case of WSF1 gene mutation-related disease with cognitive impairment as the initial symptom and recurrent cerebral infarction in the course of the disease. Brain structural imaging results suggested decreased intracranial volume, dramatically reduced in cerebral cortex and cerebellum regions. Multimodal molecular imaging results suggested Tau protein deposition in the corresponding brain regions without Aβ pathology changes. These pathological changes may indicate a role of WFS1 in neuronal vulnerability to tau pathology associated with neurodegeneration and ischemia-induced damage.